2013
DOI: 10.1007/s10886-013-0240-0
|View full text |Cite
|
Sign up to set email alerts
|

Omics Methods for Probing the Mode of Action of Natural and Synthetic Phytotoxins

Abstract: For a little over a decade, omics methods (transcriptomics, proteomics, metabolomics, and physionomics) have been used to discover and probe the mode of action of both synthetic and natural phytotoxins. For mode of action discovery, the strategy for each of these approaches is to generate an omics profile for phytotoxins with known molecular targets and to compare this library of responses to the responses of compounds with unknown modes of action. Using more than one omics approach enhances the probability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 79 publications
0
35
0
1
Order By: Relevance
“…For example, chorismate, one of the major intermediates of the shikimate pathway involving EPSPS, serves as a branch point for synthesis of various branched chain aromatic amino acids [28]. The study of the effect of herbicides on their target-sites and other related gene networks helps in deciphering the cross-talk between various biochemical pathways and the events leading to plant death [29] [30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, chorismate, one of the major intermediates of the shikimate pathway involving EPSPS, serves as a branch point for synthesis of various branched chain aromatic amino acids [28]. The study of the effect of herbicides on their target-sites and other related gene networks helps in deciphering the cross-talk between various biochemical pathways and the events leading to plant death [29] [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, under such conditions, it is clear that further, thorough and rather elaborate investigations are necessary to unequivocally determine the environmental and human health risks of use of glyphosate, its by-products and formulations. In this respect "omics" studies, such as those of Martyniuk and Simmons (2016) and Duke et al (2013), could be the most promising. Additional research is also needed on the biological functions and the regulation of the individual steps in the biosynthesis of secondary plant metabolites in order to elucidate the antagonistic (and possibly synergistic) interactions of different metabolites derived from the shikimic acid pathway.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Angelini et al ( 2015 ) reported that the allelochemicals such as linoleic, oleic and palmitic acids may offer a plausible explanation for the aggressive characteristics of the T. melanosporum and T. aestivum along with the strong cytotoxic effects observed in their brûlé (Streiblova et al 2012 ). Phytotoxic properties found within fatty acids have become part of the general knowledge in their respective fi elds of study (Duke et al 2013 ). It is believed that the mode of action in long-chain fatty acids is observable in the disruption of the cell wall building function as these can be utilised by the proteins that construct the cell walls as a sort of building block (Kim and Kim 2000 ).…”
Section: Growth Inhibitory Effects (Ir) Of Isolated Allelochemicalsmentioning
confidence: 99%